Financial reporting and statement analysis : - Stickney, Clyde P. (Dryden, 1996)
The book illustrates the effective analysis of financial statements through an integration of concepts from economics, business strategy, accounting, and other business disciplines. This analysis is accomplished by utilizing textual material based on these concepts and problems and cases built around real-world companies. The text portion of the book sets forth important concepts and analytical tools and then demonstrates their application by using the financial statements of Coca-Cola and PepsiCo